The Role of Indoxyl Sulfate in Exacerbating Colorectal Cancer During Chronic Kidney Disease Progression: Insights into the Akt/β-Catenin/c-Myc and AhR/c-Myc Pathways in HCT-116 Colorectal Cancer Cells - Yu Ichisaka; Chihiro Takei; Kazuma Naito; Manami Higa; Shozo Yano; Toshimitsu Niwa; Hidehisa Shimizu (Toxins)
Epidemiological studies suggest an increased risk of colorectal cancer (CRC) aggravation in patients with chronic kidney disease (CKD). Our previous study demonstrated that indoxyl sulfate, a uremic toxin whose concentration increases with CKD progression, exacerbates CRC through activation of the AhR and Akt pathways. Consequently, indoxyl sulfate has been proposed to be a significant link between CKD progression and CRC aggravation. The present study aimed to investigate the roles of c-Myc and β-Catenin, which are hypothesized to be downstream factors of indoxyl sulfate-induced AhR and Akt activation, in CRC cell proliferation and EGF sensitivity in HCT-116 CRC cells. Indoxyl sulfate significantly induced CRC cell proliferation at concentrations exceeding 62.5 µM, a process suppressed by the c-Myc inhibitor 10058-F4. Indoxyl sulfate activated the Akt/β-Catenin/c-Myc pathway as evidenced by the Akt inhibitor MK2206, which decreased both β-Catenin and c-Myc protein levels, and the β-Catenin inhibitor XAV-939, which reduced c-Myc protein levels. The AhR antagonist CH223191 also inhibited c-Myc upregulation, indicating involvement of the AhR/c-Myc pathway. MK2206 partially attenuated the indoxyl sulfate-induced AhR transcriptional activity, suggesting that Akt activation influences the AhR/c-Myc pathway. MK2206, CH223191, and 10058-F4 suppressed the increase in EGFR protein levels induced by indoxyl sulfate, indicating that the Akt/β-Catenin/c-Myc and AhR/c-Myc pathways enhance the sensitivity of HCT-116 CRC cells to EGF. These findings indicate that the elevation of indoxyl sulfate levels in the blood, due to CKD progression, could worsen CRC by promoting the proliferation of CRC cells and enhancing EGF signaling. Therefore, indoxyl sulfate could potentially serve as a therapeutic target for CRC aggravation in patients with CKD.